Releituras oportunas: uma (re)análise do material arqueológico coletado no âmbito de pesquisas de contrato sob a perspectiva tecnológica - sítios Itacanema I e II - Silva, André Luiz Esteves da (2020)
The present work proposes a reanalysis of the archaeological material from the Itacanema I and II sites, recovered under the Archaeological Rescue Program developed during the implementation of the Itacanema Waste Management Pole, located in the municipality of Nossa Senhora do Socorro, Sergipe. Our aim is to deepen the knowledge about the technical characteristics printed in the studied collection and to understand more about the process of occupation of the hills and hilltops of the region of the lower Cotinguiba, besides demonstrating the informative potential still existing in the archaeological material rescued in the scope contract research and that sometimes remains underutilized due to the limitations and dynamics of this type of project. In this way, we will analyze the lithic and ceramic material collected - the latter only for characterization - in a technological perspective, seeking to understand the processes that gave rise to the selected collection, through the establishment of its operative (s) chain (s) of production, understanding that this is the alternative that brings us closer to the technical capacities of the actors who produced them and, consequently, to an important part of their social behavior.